Instructors’ Awareness of the Use of Artificial Intelligence Among Higher Education Institutions in Tanzania - Ponera, Jaffar Msafiri; Stephen Madila, Shadrack (Papanda Publisher, 2024)
The study investigated the awareness of instructors about the use of AI tools in academia among higher learning institutions in Tanzania. The online questionnaires were distributed to 207 members of academic staff at Moshi Co-operative University. A total of 63 (31%) academics completed the online survey. Convenience sampling was used because the survey was shared through a WhatsApp group, which included the majority of the members of the academic staff. The study findings revealed that instructors had awareness of the use of AI tools in academia however the usage of such technology in academia is still low because it is not officially recognized in academia. The usage of AI tools was revealed to be very useful in enhancing learning and academic writing among instructors. Several AI tools that are used by instructors were identified, including ChatGPT, Bard AI, Grammaly, and Quillbolt. The study identifies several challenges such as inexperience in using AI tools, feelings that AI tools delimit thinking capacity and encourage plagiarism. The study recommends that more training be offered to instructors to create awareness about harnessing the use of AI tools. The study further recommends policies and guidelines on the use of AI tools to be formulated.